Monetary policy: regulatory news and change in the movement of financial flows - Verheliuk, Yuliia Yuriivna; Kornieiev, Volodymyr Viktorovych; Khodzhaian, Alina Oleksandrivna; Koverninska, Yuliia Viktorivna (Financial and credit activity: problems of theory and practice, 2019)
The article deals with the issues of monetary policy formation and implementation in modern conditions. The specifics of monetary regime implementation on inflation targeting in Ukraine and other countries are defined. Justified the growing role of central banks in ensuring monetary and financial stability and supporting economic growth. Revealed the modern possibilities on realization of the main function in the National Bank of Ukraine activity - ensuring the stability of the national currency. The importance of consistent meeting of monetary policy goals with the priority of price stability and the emphasis on the importance of ensuring financial stability and economic growth.

У статті розглянуті питання формування і реалізації грошово-кредитної політики у сучасних умовах. Визначені особливості впровадження монетарного режиму інфляційного таргетування в Україні та в інших країнах. Обґрунтована зростаюча роль центробанків при забезпеченні цінової і фінансової стабільності та підтримки економічного зростання. Розкриті сучасні можливості реалізації основної функції у діяльності Національного банку України – забезпечення стабільності національної валюти. Обґрунтовано важливість послідовного дотримання цілей грошово-кредитної політики з пріоритетом цінової стабільності та акцентацією важливості забезпечення фінансової стабільності та економічного зростання.
Keywords: monetary policy; monetary regime; inflation targeting; financial flows; Central Bank; government; banking regulation and supervision; interest rates; currency; price and financial stability; грошово-кредитна політика; монетарний режим; інфляційне таргетування; фінансові потоки; центробанк; уряд; банківське регулювання і нагляд; облікові ставки; валюта; цінова і фінансова стабільність